A GESTÃO DO PROGRAMA SEGUNDO TEMPO COMO POLÍTICA PÚBLICA DE ESPORTE EDUCACIONAL - JULIANA MARTA ANTUNES RAMOS (2023)
In Brazil, the possibility of a sport in its educational manifestation was contemplated in the Federal Constitution of 1988, in article 217, when recognizing sport as the duty of the State. With the aim of democratizing and guaranteeing access to sport in its educational manifestation, in 2003, the Segundo Tempo Program was created, aimed at students from public education establishments in Brazil. Based on the assumptions of analysis of social policies, inspired by the critical-dialectical method, this dissertation aimed to investigate the Segundo Tempo Program as a public policy for educational sports in terms of management from 2003 to 2019. Due to its historical and social expression, the program was configured as a relevant research object in the face of recent changes in management. This is a research with a descriptive method, with a qualitative approach, based on bibliographic research and document analysis. The results indicated that the program is based on constitutional precepts and principles that emphasize sport in its educational conception. Present in different governments, it was identified that, over the years, it received several structural and conceptual designs, as well as sought pedagogical consistency by establishing partnerships with Public Universities in the country. The program presented difficulties regarding decentralization, for more vulnerable municipalities and suffered an impact in terms of its reach from 2016 onwards. Keywords: Public Policy. Educational Policy. Social Program.